2011
DOI: 10.1155/2011/727241
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Liposomal Drug Delivery to Monocytes and Macrophages

Abstract: As the role of monocytes and macrophages in a range of diseases is better understood, strategies to target these cell types are of growing importance both scientifically and therapeutically. As particulate carriers, liposomes naturally target cells of the mononuclear phagocytic system (MPS), particularly macrophages. Loading drugs into liposomes can therefore offer an efficient means of drug targeting to MPS cells. Physicochemical properties including size, charge and lipid composition can have a very signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
214
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(221 citation statements)
references
References 107 publications
2
214
0
5
Order By: Relevance
“…But it has some shortcomings like poor scale-up, cost, short shelf life, and in some cases toxicity and off target effects. To make it long circulatory, shielding with PEG is required, and concept of stealth liposomes has risen out (Kelly et al, 2011).…”
Section: Liposomesmentioning
confidence: 99%
“…But it has some shortcomings like poor scale-up, cost, short shelf life, and in some cases toxicity and off target effects. To make it long circulatory, shielding with PEG is required, and concept of stealth liposomes has risen out (Kelly et al, 2011).…”
Section: Liposomesmentioning
confidence: 99%
“…The negatively charged lipid was used to prepare anionic liposomal formulations in order to prevent the aggregation of liposomes due to electrostatic repulsion [24,30,31]. Furthermore, it was reported that the presence of negatively charged lipids in liposomes, allows rapid uptake by the reticuloendothelial system [24], while large and positively charged liposomes induce cytokine activation and toxicity and thereby their safety for clinical use is limited [32].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the fast clearance of liposomes to the liver is most probably due to the presence of the positively charged DOTAP in the liposome formulation, which could lead to recognition by the macrophages (Kelly et al, 2011). Our theory was that the presence of DTPA on the surface would shield the charge from the blood compartment.…”
Section: Scintigraphic Imaging Studymentioning
confidence: 87%